Asymmetric Coordination Toward a Photoinduced Single‐Chain Magnet Showing High Coercivity Values. (30th March 2021) - Liu, Qiang; Hu, Ji‐Xiang; Meng, Yin‐Shan; Jiang, Wen‐Jing; Wang, Jun‐Li; Wen, Wen; Wu, Qiong; Zhu, Hai‐Lang; Zhao, Liang; Liu, Tao
Abstract: The production of photo‐switchable molecular nanomagnets with substantial coercivity, which is indispensable for information storage and process applications, is challenging. Introducing photo‐responsive spin‐crossover units provides a feasible means of controlling the magnetic anisotropy, interactions, and overall nanomagnet properties. Herein, we report a cyanide‐bridged chain 1⋅12H2 O ([( Pz Tp)Fe III (CN)3 ]2 Fe II (Pmat)2 n ⋅12 H2 O) generated by linking the Fe II ‐based spin‐crossover unit with the [( Pz Tp)Fe(CN)3 ] − ( Pz Tp: tetrakis(pyrazolyl)borate) building block in the presence of asymmetric ditopic ligand Pmat ((4‐pyridine‐4‐yl)methyleneamino‐1, 2, 4‐triazole). Structural characterization revealed that the introduction of this asymmetric ligand led to a distorted coordination environment of Fe II ions, which were equatorially coordinated by four cyanide N atoms, and apically coordinated by one pyridine N atom and one triazole N atom. Upon 808‐nm light irradiation, 1⋅12H2 O underwent photoinduced spin‐crossover and exhibited single‐chain magnet behavior with a coercive field of up to 1.3 T. This represents a 3d‐based photoinduced single‐chain magnet exhibiting pronounced hysteresis. Abstract : A light‐induced spin‐crossover switchable single‐chain magnet was discovered in an asymmetric ditopic ligand‐containing cyanide‐bridged compound. A photoinduced opening hysteresis with the highest coercive field of 1.3 T was realized in pure 3d metal‐based molecular magnets.